EXTH-96. BIOPROCESSING OF SURGICAL PEDIATRIC BRAIN TUMOR SPECIMENS FOR GENOME-GUIDED PERSONALIZED DRUG TESTING. (14th November 2022) - Nasajpour, Emon; Lyle, Geoff; Lancero, Hope; Garcia, Cesar; Learned, Katrina; Gibson, Eden; Tran, Caitlynn; Schouten, Troy; Vogel, Hannes; Mahaney, Kelly; Prolo, Laura; Vaske, Olena; et al.
Abstract: Novel treatment approaches for pediatric central nervous system (CNS) tumors are urgently needed. A lack of patient-derived tumor cells impedes progress towards developing such new therapies. We intended to overcome this challenge by establishing methods to create a biorepository of viable single cell suspensions of pediatric brain tumor surgical specimens. Quantitative and qualitative comparisons of tissue processing strategies were performed to preserve viability of heterogeneous tumor and immune cells. Novel drug targets were identified by analyzing pathways affected by RNA transcripts that are highly expressed (outliers) in a patients' tumor; outliers for each patient were determined by RNA-seq data from individual patients' tumors compared with a compendium of 12, 747 pediatric and adult samples harmonized by the Treehouse Childhood Cancer Initiative at the UCSC Genomics Institute. The predicted anti-tumor efficacy of small molecule inhibitors of the outlier pathways was tested in cell viability assays against short-term cultured cells from matched patients. Successful tissue collection required obtaining informed consent, standard operating procedures, and sample recording using a Laboratory Inventory Management Software (LIMS). Since 2020 we have banked 67 pediatric CNS brain tumor specimens at Stanford. Amongst those, 51 cases yielded sufficient tissue for RNA-seq and cryoprotection. The most common tumor histology was low-grade glioma (LGG, 26 of 67), the majority of which were pilocytic astrocytoma (18 of 26). The second and third most common tumor types are embryonal tumors (6 medulloblastoma, 3 AT/RT) and ependymoma (4), respectively. We identified significant differences in cell viability with different preservation media. An outlier pathway previously not implicated in LGG was identified and sensitivity to a small molecule inhibitor of this outlier pathway was demonstrated. Taken together, we established feasibility for validating therapeutic vulnerabilities identified by a genome-guided approach in short-term cultures from surgical specimens. This works facilitates the rapid development of personalized CNS tumor treatment.